Lesões cariosas com sombreamento em dentina (ICDAS 4) em adolescentes e adultos jovens de Santa Maria, RS - Marquezan, Patricia Kolling (2021)
This thesis is composed of three scientific articles whose objectives were to assess the prevalence, extent, risk indicators and intraoral distribution of underlying dentin shadows (UDS) (ICDAS 4 caries lesions) in a representative sample of 15-19-year-old adolescents from southern Brazil (Article I), to evaluate the association between UDS and oral health-related quality of life (OHRQoL) in the same sample of adolescents aged 15-19 years (Article II) and to study the progression of (UDS) in permanent posterior teeth over 1-2 years (Article III). Articles I and II derived from a population-based epidemiological study that evaluated a representative sample of the population of adolescents aged 15-19 years from Santa Maria, RS. Adolescents were clinically examined at the school environment for clinical characteristics and the OHRQoL was assessed using the OHIP-14 questionnaire. Article III was a prospective cohort stury that followed patients with UDS for a period of 1-2 years. Data analysis was performed in Articles I and II using multilevel Poisson regression models, whereas in Article III negative binomial regression models with generalized estimating equations were used due to the presence of clustered data. In Article I, the prevalence of UDS was low (8.8%), corresponding to 106 students. On average, this population had 0.13 lesions. The most affected teeth were the lower first molars followed by the upper first molars. The adjusted model showed that caries activity, age (≥17 years) and family income were significantly associated with the occurrence of UDS. In Article II, it was observed that UDS were negatively associated with OHRQoL in adolescents aged 15-19 years, being this effect dependent on the number of lesions. Adolescents who had 3-4 UDS lesions had a mean OHIP-14 score 35% higher than those without UDS, indicating poorer OHRQoL. Of the 7 domains, UDS were associated with the physical disability, psychological disability, social disability and handicap domains in the adolescent population under investigation (15-19 years). In relation to Article III, low progression rates were observed, being only 7% after 1 year (8/115) and 16.2% after 2 years (12/74). The risk analysis demonstrated that the subjects' skin color (non-white) and the presence of radiolucency at baseline were associated with lesion progression. The results presented in these articles show the low rates of prevalence/extent of UDS in the evaluated population and its association with caries activity and socio-demographic variables (Article I), its potential negative impact on HRQoL (Article II) and the low rates of progression of this type of lesion over 1-2 years, being associated with the individual's skin color and the presence of radiolucency on the baseline radiograph (Article III).